2017
DOI: 10.1177/1098612x17705044
|View full text |Cite
|
Sign up to set email alerts
|

Pain and adverse behavior in declawed cats

Abstract: Objectives The aim of this study was to assess the impact of onychectomy (declawing) upon subsequent development of back pain and unwanted behavior in cohorts of treated and control cats housed in two different locations. Methods This was a retrospective cohort study. In total, there was 137 declawed and 137 non-declawed cats, of which 176 were owned cats (88 declawed, 88 non-declawed) and 98 were shelter cats (49 declawed and 49 non-declawed). All cats were physically examined for signs of pain and barbering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
0
35
0
1
Order By: Relevance
“…Specific reports of similar chronic pain related problem aggression in cats appear to be missing in the literature, but such responses are believed to occur in relation to both arthritis and dental disease [11][12][13][14] and typically manifest as poorer mood [13] and defensiveness in relation to interaction [13,15,16] but also increased fearfulness in some cases [13]. A retrospective cohort study of 137 declawed cats indicated that declawed cats were at increased risk (odds ratio of 2.66) of having back pain and nearly nine times more likely to show signs of aggression [17]. Central sensitization (sometimes called "wind-up pain"), in which there is increased sensitivity towards pain in body regions not initially affected by a painful lesion, is also believed to occur in the cat, resulting in aggression when touched in this non-painful region [18]; the absence of a lesion associated with the area may lead to the mistaken supposition that the cat's problem is "behavioral" rather than pain-related.…”
mentioning
confidence: 99%
“…Specific reports of similar chronic pain related problem aggression in cats appear to be missing in the literature, but such responses are believed to occur in relation to both arthritis and dental disease [11][12][13][14] and typically manifest as poorer mood [13] and defensiveness in relation to interaction [13,15,16] but also increased fearfulness in some cases [13]. A retrospective cohort study of 137 declawed cats indicated that declawed cats were at increased risk (odds ratio of 2.66) of having back pain and nearly nine times more likely to show signs of aggression [17]. Central sensitization (sometimes called "wind-up pain"), in which there is increased sensitivity towards pain in body regions not initially affected by a painful lesion, is also believed to occur in the cat, resulting in aggression when touched in this non-painful region [18]; the absence of a lesion associated with the area may lead to the mistaken supposition that the cat's problem is "behavioral" rather than pain-related.…”
mentioning
confidence: 99%
“…17 However, one study found that 63% of the onychectomized cats evaluated had P3 fragments left behind at the time of surgery, and those cats were the most at risk for postoperative complications related to the onychectomy procedure. 16…”
Section: Discussionmentioning
confidence: 99%
“…Onychectomy has been linked with numerous complications, including pain, 14,3234 infection, 14,33,35 hemorrhage, 33,35 swelling, 33 lameness, 14,3335 incomplete healing, 35 reluctance to jump, 14 reluctance to scratch, 14 chewing at the digits, 14 neuropathic pain, 14 neuropraxia, 35 claw regrowth, 14,16,3335 protrusion of the second phalanx, 33,35 callused and misshapen toe pads, 33,35,36 tissue necrosis, 35 increased aggression and biting behavior, 37 inappropriate elimination, 16,34,37 back pain, 16 muscle loss, 34 barbering, 16 and flexor tendon contracture. 36,38 Based on the current case, neoplasia may also be considered a potential complication of onychectomy in cats.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical methods and adherence to appropriate technique affect the outcome for declawing, as with all surgeries. A recent study demonstrated that 63% of cats had radiographic evidence of P3 remnants, and this was most highly correlated with back pain, periuria, and aggression (128). These results were seen far out from the surgery date.…”
Section: Declawing (Onychectomy)mentioning
confidence: 98%
“…It should come as no surprise that evidence shows declawing causes pain in cats, in part due to a number of surgical sequelae including retained bone fragments, osteomyelitis, excessive tissue handling during surgery, and complications from bandaging (124). While pain is an expected outcome of any surgery and should be ameliorated appropriately, there is evidence that there is short-and long-term pain due to onychectomy (124)(125)(126)(127)(128)(129). Behaviors indicative of pain, such as forepaw shaking and laying on their side, were seen in cats that were declawed compared to those having a sham procedure performed (125).…”
Section: Declawing (Onychectomy)mentioning
confidence: 99%